Multinuclear MRS at 7T Uncovers Exercise Driven Differences in Skeletal Muscle Energy Metabolism Between Young and Seniors - Krumpolec, Patrik; Klepochová, Radka; Just, Ivica; Tušek Jelenc, Marjeta; Frollo, Ivan; Ukropec, Jozef; Ukropcová, Barbara; Trattnig, Siegfried; Krššák, Martin; Valkovič, Ladislav (Frontiers in Physiology, 2020)
Purpose: Aging is associated with changes in muscle energy metabolism. Proton (1H) and phosphorous (31P) magnetic resonance spectroscopy (MRS) has been successfully applied for noninvasive investigation of skeletal muscle metabolism. The aim of this study was to detect differences in adenosine triphosphate (ATP) production in the aging muscle by 31P-MRS and to identify potential changes associated with buffer capacity of muscle carnosine by 1H-MRS. Methods: Fifteen young and nineteen elderly volunteers were examined. 1H and 31P-MRS spectra were acquired at high-field (7T). Investigation included carnosine quantification using 1H-MRS and resting and dynamic 31P-MRS, both including saturation transfer measurements of phosphocreatine (PCr)- and inorganic phosphate (Pi)-to-ATP metabolic fluxes. Results: Elderly volunteers had higher time constant of PCr recovery (τPCr) in comparison to young. Exercise was connected with significant decrease of PCr-to-ATP flux in both groups. Moreover, PCr-to-ATP flux was significantly higher in young compared to the elderly both, at rest and during exercise. Similarly, an increment of Pi-to-ATP flux with exercise was found in both groups but the intergroup difference was only observed during exercise. Elderly had lower muscle carnosine concentration and lower post-exercise pH. Strong increase of phosphomonoester (PME) concentration was observed with exercise in elderly and faster Pi:PCr kinetic was found in young volunteers compared to elderly during the recovery period. Conclusion: Observation of a massive increment of PME concentration together with high Pi-to-ATP flux during exercise in seniors refer to decreased ability of muscle to meet the metabolic requirements of exercise and thus a limited ability of seniors to effectively support the exercise load.